Peptide-Decorated Supramolecules for Subcellular Targeted Cancer Therapy: Recent Advances - Jin, Hua; Lin, Xiao; Gao, Mengyue; Cui, Liao; Liu, Yun (Frontiers in Chemistry, 2020)
Binding of small molecules through non-covalent molecular forces affords supramolecules, such as hydrogen bonds, electrostatic, π-π interactions, van der Waals forces and hydrophobic effects. Due to their good biocompatibility, low immunogenicity and biodegradability, supramolecules have been intensely studied as multifunctional drug delivery platforms in targeted cancer therapy. In consideration of the defective therapeutic efficacy induced by simple transporting the therapeutic agents into tumor tissues or cancer cells instead of subcellular organelles, research is progressing towards the development of subcellular targeted cancer therapy (STCT) strategies. STCT is one of the most recent developments in the field of cancer nanomedicine. It is defined as the specific transportation of therapeutic agents to the target organelles for cancer treatment, which makes therapeutic agents accumulate in the target organelles at higher concentrations than other subcellular compartments. Compared with tumor-targeted and cancer-cell-targeted therapies, STCT exhibits dramatically improved specificity and precision, diminished adverse effects, and enhanced capacity to reverse multidrug resistance (MDR). Over the past decades, peptides have played increasingly essential roles in multi-types of tumor-targeted drug delivery systems. Moreover, peptide-mediated STCT is becoming an emerging approach for precision cancer therapy and has been used in various cancer treatments, such as photothermal therapy (PTT), photodynamic therapy (PDT), chemotherapy, gene therapy and non-drug-loaded nanoassemblies. In this review, we will focus on recent innovations in the variety of peptides used in designing peptide-decorated supramolecules for cell-membrane-, mitochondria- and nucleus-localized STCT.